Recent Study on Speed Control for DC Encoder Motor and Path Optimization in an Automated Guided Vehicle - Chavan, Madhuri; Maya, G. (New Approaches in Engineering Research Vol. 2, 2021)
In the fields of automotive and logistics, the automated guided vehicle (AGV) offers a wide range of applications.AGV should run at a steady speed to ensure plant stability. To achieve constant speed, the AGV uses a DC encoder motor that is controlled by a Fuzzy controller and a PID controller. The system's response is achieved using a fuzzy controller and a PID controller. The fuzzy logic controller reduces the system's steady-state inaccuracy and overshoot. The Dijkstra algorithm is used to select the optimal path. The shortest path between the source and destination nodes is determined by this algorithm.